1995
DOI: 10.1002/(sici)1097-4571(199510)46:9<685::aid-asi5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

An associative model of word selection in the generation of search queries

Abstract: To generate a search query based on a end-user request, a database searcher has to select appropriate search terms. These terms can either be taken from the request, or they can be added by the searcher. This selection process is simulated by an associative lexical net; the nodes of the net are the terms used in 94 records of written requests to a psychological information agency and the respective on-line searches. The weights connecting the nodes are calculated from the co-occurrences of these terms in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In information retrieval, statistical term association techniques based on term co-occurrences have been widely applied to automatic thesaurus construction (Chen & Lynch, 1992;Grefenstette, 1994;Park & Choi, 1995;Salton & Lesk, 1971) and query expansion (Ferber et al, 1995;Gauch & Wang, 1997;Kim & Choi, 1999;Kwon et al, 1994;Minker et al, 1972). As a somewhat different application, an association-based method was proposed for automatic indexing with a controlled vocabulary (Plaunt & Norgard, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In information retrieval, statistical term association techniques based on term co-occurrences have been widely applied to automatic thesaurus construction (Chen & Lynch, 1992;Grefenstette, 1994;Park & Choi, 1995;Salton & Lesk, 1971) and query expansion (Ferber et al, 1995;Gauch & Wang, 1997;Kim & Choi, 1999;Kwon et al, 1994;Minker et al, 1972). As a somewhat different application, an association-based method was proposed for automatic indexing with a controlled vocabulary (Plaunt & Norgard, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Kelly and Fu (2006) looked at use of words in queries that had appeared in the interface or come from suggestions formulated by human users; their results suggest that more terms came from the interface than from users. Ferber, Wettler, and Rapp (1995) used a lexical net to simulate the associative processes involved in word choice during QF. Smith and Wacholder (2010) have recently suggested that the very processing of the query may sometimes inhibit users from recognizing the potential usefulness of related words.…”
Section: Queriesmentioning
confidence: 99%
“…To‐date, most research in information science has focused on sources of query terms external to the user; examples are the description of the information need, the list of search results, recently viewed web pages, query terms suggested by the search system, and search intermediaries (e.g., Kelly & Fu (2006), Vakkari (2002), Ferber et al (1995), and Spink (1994)). However, there is another source of query terms internal to the user – the individual's own lexical knowledge.…”
Section: Introductionmentioning
confidence: 99%